Relationship between work motivation scale and TPACK. (18th July 2019) - Fernandes, Semila; Gupta, Pooja; Kumar, V.V. Ajith
Abstract : Purpose: The purpose of this paper is to measure the academic motives of faculty in higher education to understand the pattern of relationships between work motivation scale (WMS) and technological pedagogical content knowledge (TPACK). Design/methodology/approach: The research adopts regression analysis to help model the data collected from 63 faculty members from India. The empirical study investigated the relationship of intrinsic motivation (IntrM), integrated motivation (InteM), identified motivation (IdenM), introjected motivation (IntrjM), external regulation motivation (ExtR) and amotivation (Amot) with each of technological knowledge (TK), (pedagogical knowledge (PK), content knowledge (CK) and TPACK. Findings: Optimal functioning among faculty was due to "InteM" followed by "IntrM" and "IdenM" that yielded most positive consequence (mean values>3.9). "ExtR" and "Amot" were the negative outcomes that would be counterproductive and result in employee dejection (Mean values<3.1). The results proved that all TPACK variables were positively related to "IntrM" – a self-determined motivation. Additionally, "TK" and "PK' were positively related to "IntrjM" – a behavior that is regulated by self-esteem and self-worth; "TPACK" depicted positive relationship with "IntrjM" and negative correlation with "IdenM." Research limitations/implications: The study supported the fact that TPACK and WMS when analyzed together can create better engagement models among the faculty for an enriching learner experience interaction. Furthermore, it would help identify specific strategies on teacher development training programs through the integration of technology. Originality/value: The study is original and seeks to inspect the relationship between TPACK and WMS among faculty of higher education in Indian business schools.